Time-Course Transcriptional and Chromatin Accessibility Profiling Reveals Genes Associated With Asymmetrical Gonadal Development in Chicken Embryos - Li, Jianbo; Sun, Congjiao; Zheng, Jiangxia; Li, Junying; Yi, Guoqiang; Yang, Ning (Frontiers in Cell and Developmental Biology, 2022)
In birds, male gonads form on both sides whereas most females develop asymmetric gonads. Multiple early lines of evidence suggested that the right gonad fails to develop into a functional ovary, mainly due to differential expression of PITX2 in the gonadal epithelium. Despite some advances in recent years, the molecular mechanisms underlying asymmetric gonadal development remain unclear. Here, using bulk analysis of whole gonads, we established a relatively detailed profile of four representative stages of chicken gonadal development at the transcriptional and chromatin levels. We revealed that many candidate genes were significantly enriched in morphogenesis, meiosis and subcellular structure formation, which may be responsible for asymmetric gonadal development. Further chromatin accessibility analysis suggested that the transcriptional activities of the candidate genes might be regulated by nearby open chromatin regions, which may act as transcription factor (TF) binding sites and potential cis-regulatory elements. We found that LHX9 was a promising TF that bound to the left-biased peaks of many cell cycle-related genes. In summary, this study provides distinctive insights into the potential molecular basis underlying the asymmetric development of chicken gonads.